Nonlinear electric polarization in wurtzite group III-nitrides - Vaschenko, Georgiy O., author; Menoni, Carmen, advisor; Rocca, Jorge, committee member; Robinson, Gary, committee member; Levinger, Nancy, committee member (Colorado State University. Libraries, 2002)
In this dissertation we provide the first experimental investigation of the nonlinear piezoelectric effect in technologically important group IIl-nitride heterostructures with wurtzite crystal lattice configuration. This effect is revealed by modifying the strain state in the InGaN/GaN and GaN/AlGaN quantum well structures by applied hydrostatic pressure. The ensuing changes in the electric polarization are probed with time-integrated and time-resolved photoluminescence spectroscopy. From the photo-luminescence peak energy of the quantum well emission at different applied pressures we obtain the values of the polarization-induced built-in electric field in the wells and the corresponding well-barrier polarization difference. We found that in the InGaN/GaN and GaN/AlGaN quantum well structures the built-in field increases with applied pressure much faster than expected from the conventional (linear) model of macroscopic polarization in group III-nitrides. In the InGaN/GaN structures the built-in field increases from ~ 1.4 MV/cm at atmospheric pressure to ~ 2.6 MV/cm at 9 GPa, while the theory predicts a reduction of the field to ~ 1.3 MV/cm. This discrepancy is interpreted as the signature of the strong nonlinearity of the piezoelectric response in the group III-nitrides. Model calculations incorporating the strain dependence of the piezoelectric coefficients of the investigated materials reproduce reasonably well the experimentally observed pressure behavior of the built-in electric field. Other secondary effects, such as nonlinear elasticity and photoelastic effect, have also been included in this model and are shown to have a significantly smaller effect on the observed changes in the photoluminescence with pressure. We conclude that the nonlinear piezoelectric effect plays the dominant role in defining the pressure behavior of photoluminescence in the InGaN/GaN and GaN/AlGaN quantum well structures.

The findings of this work reveal the large scale of the nonlinear piezoelectric effect in group III-nitrides and challenge the accuracy of the conventional theory of macroscopic polarization in these materials. We show that for the accurate modeling of the nitride-based devices the nonlinear piezoelectricity should be accounted for. Also, this work for the first time unequivocally identifies the polarization-induced electric field as the mechanism responsible for the anomalous pressure behavior in the InGaN/GaN and GaN/AIGaN quantum well structures.
Keywords: electrical engineering